Evaluation of the Fungitoxic Activity of Copaiba Oil (Copaifera spp.) from Western Amazon against Anthracnose (Colletotrichum gloeosporioides (Penz.) Penz. & Sacc.) on Papaya (Carica papaya L.) (Research, Society and Development, 2023)
The genus Copaifera is not only relevant to the timber industry but also stands out for its resin oil, a transparent, viscous, and fragrant exudate. This product, commonly used in folk medicine, symbolizes the wealth of forest-derived products and their appreciation. In line with the Sustainable Development Goals (SDGs) metrics, it is essential that its exploitation is linked to sustainability, promoting regional development, and emphasizing the importance of protecting and valuing the region's natural resources. Therefore, the objective of this study was to evaluate the physicochemical characteristics of Copaiba resin oil varieties collected at farmers' markets and assess its fungicidal potential in controlling Colletotrichum gloeosporioides, the causative agent of papaya anthracnose (Carica papaya). The fungus Colletotrichum gloeosporioides was isolated from diseased papaya fruits. The following treatments were used: a control and doses of 50, 100, 150, and 200 μL/mL of Copaiba oil, with each dose incorporated into 20 mL of PDA (Potato, Dextrose, and Agar) culture medium, to determine the effect of the oil on the mycelial growth of the phytopathogen. The data were subjected to analysis of variance (ANOVA) and regression analysis. When evaluating the effect of oil varieties, it was found that the greatest inhibitory effect was observed for variety 2, with the highest inhibition power caused by doses of 100 and 200 μL/mL in variety 2.